2018
DOI: 10.1007/s11906-018-0850-6
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, Short Sleep Duration, and High Blood Pressure: Recent Evidence and Future Directions for the Prevention and Management of Hypertension

Abstract: Evidence indicates that the association between insomnia and elevated blood pressure (BP) or stage 1 and 2 hypertension is stronger in those with chronic insomnia, as compared to those with isolated insomnia symptoms, and primarily found in those with the insomnia with objective short sleep duration phenotype. There is a key gap in ambulatory BP monitoring across the sleep-wake cycle as well as in randomized clinical trials testing the effectiveness of pharmacological or cognitive-behavioral insomnia therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 50 publications
4
31
0
6
Order By: Relevance
“…Future studies should adopt a longitudinal study design or use qualitative methods to understand the cause-and-effect relationships between sleep duration and physical fitness. Third, it is suggested that sleep quality is influenced by age, gender, health status, and the lack of information on insomnia, depression, stress levels, and other relevant phenomena [35][36][37]. Although the present study controlled for these confounding factors during the analysis, we suggest future studies focus on a more specific population in terms of the relationship between sleep duration and physical fitness in older adults.…”
Section: Discussionmentioning
confidence: 82%
“…Future studies should adopt a longitudinal study design or use qualitative methods to understand the cause-and-effect relationships between sleep duration and physical fitness. Third, it is suggested that sleep quality is influenced by age, gender, health status, and the lack of information on insomnia, depression, stress levels, and other relevant phenomena [35][36][37]. Although the present study controlled for these confounding factors during the analysis, we suggest future studies focus on a more specific population in terms of the relationship between sleep duration and physical fitness in older adults.…”
Section: Discussionmentioning
confidence: 82%
“…Short sleep duration in subjects with ID may indicate a severe phenotype of ID (Vgontzas, Fernandez‐Mendoza, Liao, & Bixler, ) and is associated with systemic hypertension (Bathgate & Fernandez‐Mendoza, ; Bathgate, Edinger, Wyatt, & Krystal, ; Vgontzas, Liao, Bixler, Chrousos, & Vela‐Bueno, ), impaired heart rate variability (de Zambotti, Covassin, Min Tona, Sarlo, & Stegagno, ), diabetes mellitus (Vgontzas, Liao, Pejovic, et al, ), reduced brain metabolite concentration (Miller et al, ) and even increased mortality (Vgontzas et al, ). The current study was prompted by the aforementioned growing evidence of the detrimental effect of hyperarousal and objective short sleep duration on individuals with ID.…”
Section: Introductionmentioning
confidence: 99%
“…These findings emphasize that tests targeting complex neurocognitive tasks, rather than simple neurocognitive tasks, are more sensitive to the deficit in patients with ID, and provided preliminary evidence that symptomatic individuals ID and hyperarousal state are more prone to neurocognitive deficits than ID sufferers who are asymptomatic and not physiologically hyperaroused. Short sleep duration in subjects with ID may indicate a severe phenotype of ID (Vgontzas, Fernandez-Mendoza, Liao, & Bixler, 2013) and is associated with systemic hypertension (Bathgate & Fernandez-Mendoza, 2018;Bathgate, Edinger, Wyatt, & Krystal, 2016;Vgontzas, Liao, Bixler, Chrousos, & Vela-Bueno, 2009), impaired heart rate variability (de Zambotti, Covassin, Min Tona, Sarlo, & Stegagno, 2011), diabetes mellitus (Vgontzas, Liao, Pejovic, et al, 2009), reduced brain metabolite concentration (Miller et al, 2017) and even increased mortality . The current study was prompted by the aforementioned growing evidence of the detrimental effect of hyperarousal and objective short sleep duration on individuals with ID.…”
mentioning
confidence: 99%
“…Accumulating evidence suggests that insomnia is associated with a wide cluster of cardiovascular and metabolic disorders, such as coronary heart disease, stroke, hypertension, diabetes mellitus, obesity, dyslipidemia, atherosclerosis, heart failure, and arrhythmias . With regard to hypertension, few data suggest that both the diagnosis of insomnia and the severity of the sleep disturbance (such as cortical hyper‐arousal common in insomnia) are associated with over‐activation of the hypothalamic‐pituitary‐adrenal axis and over‐secretion of cortisol, and thus may result in abnormalities in circadian regulation of blood pressure (BP), and non‐dipping status . Furthermore, up‐regulation of the sympathetic system, the immune system, and the inflammatory cascade (altogether, the atherogenic trinity) in insomnia, might contribute to hypertension, as well.…”
Section: Studies On Insomnia Conducted Over the Last 2 Y Evaluating mentioning
confidence: 99%